Mapping and Monitoring Forest Cover - Congalton, Russell G. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a compilation of six papers that provide some valuable information about mapping and monitoring forest cover using remotely sensed imagery. Examples include mapping large areas of forest, evaluating forest change over time, combining remotely sensed imagery with ground inventory information, and mapping forest characteristics from very high spatial resolution data. Together, these results demonstrate effective techniques for effectively learning more about our very important forest resources.